The Study of Religious Interpretation and Expression; - Arifuddin, Arifuddin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2022)
This study discusses the Religious Moderation Construction of Islamic Boarding Schools in Palopo City with a focus on religious interpretation and expression. The research was carried out at the DatokSulaiman Putra Palopo Islamic Boarding School and the Hidayatullah Islamic Boarding School Palopo. This study aims to determineinterpretation of religious moderation and religious expression of Islamic boarding schools in the city of Palopo. The type of research used is descriptive qualitative. Basically, qualitative research seeks to describe, analyze, and interpret the data collected in the research process. The results of the research obtained in the field are the interpretation of religious moderation in the DatokSulaiman Putra Modern Islamic Boarding School and the HidayatullahPalopo Islamic Boarding School, as follows: 1) The vision of the state, as a form of attitude and behavior related to the vision of the state in the pesantren, namely: Attitudes of nationalism, love for the homeland , The use of school attributes according to the rules, and discipline. 2) Multiple awareness, as a form of attitude and behavior related to plural awareness in Islamic boarding schools, namely: working with various institutions, rejecting radicalism, mutual respect and respect, and tolerance between religious communities. 3) Respect for human values, as a form of attitude and behavior related to respect for human values ​​in Islamic boarding schools, namely: there is no dichotomization of students, both from the aspect of social status, economy, even ethnicity, not discriminatory in service, and respect fellow students and teachers. 4) Appreciation of cultural values ​​and identity, as a form of attitude and behavior related Appreciation of Cultural Values ​​and Identity in Islamic boarding schools, namely visiting historical places in the city of Palopo, local traditional activities such as barasanjitahlilan and others related to religion, as well as attending celebrations or traditional events carried out by the community. Expressions of diversity in the DatokSulaiman Putra Modern Islamic Boarding School and the HidayatullahPalopo Islamic Boarding School, namely: expressions of ceremonial activities as a form of nationalism and love for the homeland, expressions in humanitarian mission activities, expressions on anti-violence socialization activities, expressions on religious tourism activities, expressions on religious tradition activities, expression in the form of mental and spiritual strengthening, and expression in the form of integral activities. The interpretation of religious moderation is in line with religious expressions in cultivating the moderate values ​​of Islamic boarding schools in Palopo City, especially the DatokSulaiman Putra Modern Islamic Boarding School and the HidayatullahPalopo Islamic Boarding School. So that the two pesantren take part and contribute in constructing religious moderation in the city of Palopo.